Facile Fabrication of Sodium Titanate Nanostructures Using Metatitanic Acid (TiO2·H2O) and Its Adsorption Property. (18th January 2012) - Li, Gang; Zhang, Lide; Fang, Ming
Abstract : Fluffy sodium titanate nanostructures have been fabricated by a simple hydrothermal method with metatitanic acid as precursor. The obtained nanostructures exhibit as the aggregation of nanosheets, and the surface area of the nanostructure is about 110.59 m 2 /g. Such nanoarchitecture indicates high adsorption capacity to some metal ions, such as Cd 2+, and the maximum adsorption capacity has been estimated to be 255.18 mg/g. The possible reasons that are responsible after its high adsorption ability, have been ascribed to the tiny structure, the ion-exchange ability and the large surface area of the sodium titanate nanostructures. And this may greatly enlarge its application potential as an adsorbent.